2016
DOI: 10.4103/0974-8237.181878
|View full text |Cite
|
Sign up to set email alerts
|

Late onset leptomeningeal and whole spine metastasis from supratentorial Glioblastoma multiforme: An uncommon manifestation of a common tumor

Abstract: Glioblastoma multiforme (GBM) is one of the most common and aggressive primary brain tumors, composing 12-20% of all the intracranial tumors in adults with a highly malignant course and average life expectancy of approximately 12-14 months following initial diagnosis. Leptomeningeal or intramedullary metastasis from primary GBM is a rare phenomenon with a poor prognosis. We present a rare case of GBM with late onset intramedullary, extramedullary, as well as leptomeningeal spinal metastasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Besides, a study of 18 pediatric patients by Karremann et al showed no significant difference in median age, male preference, median clinical history, and prognosis between GCG and GBM [7]. Spinal metastasis from primary GBM is extremely rare and occurs relatively late [18,19]. Treatment modalities include surgery for decompression, RT in total dose of 25-40 Gy and intrathecal CH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, a study of 18 pediatric patients by Karremann et al showed no significant difference in median age, male preference, median clinical history, and prognosis between GCG and GBM [7]. Spinal metastasis from primary GBM is extremely rare and occurs relatively late [18,19]. Treatment modalities include surgery for decompression, RT in total dose of 25-40 Gy and intrathecal CH.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, RT is used most commonly. There is no obvious survival advantage of one therapy over the other and the prognostic is poor [18,19].…”
Section: Discussionmentioning
confidence: 99%